Behavior, long-term stress and relationship to owner in relinquished dogs - Sulonen, Cornelia; Löf, Jenny; Jensen, Per; Lasses, Karolina; Theodorsson, Elvar; Quist, Helena; Roth, Lina S. V. (Frontiers in Animal Science, 2024)
Dog ownership gained popularity during the pandemic. However, there was also a corresponding increase in the number of dogs being relinquished and rehomed. The rehoming procedure is known to be stressful to the dog, but the short-and long-term effects still need to be better understood. This study aimed to enhance our understanding of the short-and longterm challenges dogs encounter during the rehoming process by combining behavioural and physiological measures. The study included 20 relinquished dogs from a Swedish shelter and 30 rehomed dogs, comparing them to 33 control dogs that have been with their owner since leaving the breeder as puppies. All participants performed an unsolvable problem task, eyecontact test, and memory test and hair samples were obtained to analyze cortisol concentrations. Furthermore, dog owners (of rehomed and control dogs) completed a questionnaire assessing their perceived human-dog relationship. These owner-dog dyads also participated in a behavioral synchronization test. The result indicated that shelter dogs had the shortest eye-contact duration in both an eye-contact test and an unsolvable problem task, but there was no difference between the three groups in the short-term memory test or in stressrelated behaviors. Analysis of hair cortisol concentrations in the dogs revealed that the shelter dogs had higher long-term stress levels than rehomed dogs, but they did not differ significantly from control dogs. Both rehomed and control dogs synchronized their behavior with their owner, but, interestingly, the owners of rehomed dogs reported a higher emotional closeness to their dogs than owners of control dogs. Consequently, despite the observed shortterm effects during the rehoming procedure, this study suggests that rehomed dogs can adapt to their new life and develop a strong relationship with their owner.